PERANCANGAN MANAJEMEN LAYANAN TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK INFORMATION TECHNOLOGY INFRASTUCTURE LIBRARY (ITIL) VERSI 3 DOMAIN SERVICE OPERATION STUDI KASUS DI SMK NEGERI 3 BANDUNG - Siti Nur; Jajat Sudrajat (STMIK Mardira Indonesia, Bandung, 2020)
Information Technology (IT) is one of the most powerful pillars in a company while many functions cannot be managed without IT. Nowadays IT is becoming a technology that is widely used by most organizations and is expected to help improve ongoing processes, and be controlled in the field of education. School is one of education with one of the tasks it carries is to provide services to the community to provide quality and efficient future Human Resources (HR). The main activity in the school in accordance with the specified function, namely as an education provider, is an academic service. This study discusses one of the information technology governance work agreements, ITIL (IT Infrastructure Library) version 3. This framework provides best practice guidelines for IT Service Management. One of the cycles in ITIL version 3 is IT Service Operations which is the focus area of this research. From the results of a survey conducted on IT and Non-IT Students, IT and Non-IT teachers as well as IT and Non-IT employees regarding their responses to the readiness requirements for implementing IT Service Operations at SMK Negeri 3 Bandung, it is necessary to have time in the game now. initial and repetitive where current improvements still need to be done Steps related to the implementation of IT Service Operations. In this study preparations have been made in the steps, strategies and evaluation of improvements for the application of IT Service Operations at SMK Negeri 3 Bandung by using IT Infrastructure Library (ITIL) version 3. The final result of this thesis is a clue / clue related to the steps , strategies and evaluation of improvements that need to be done before implementing the activities and processes of IT Service Operations at SMK Negeri 3 Bandung. This result is the answer to overcome the weaknesses found in the management of information technology management, especially IT Service Operations regarding academic services at SMK Negeri 3 Bandung.Keywords: ITIL version 3, service operation, academic services DOI : http://doi.org/10.5281/zenodo.3929081